Environmental Protection Through Sustainability Clauses in Contract Law - Iroda Bakhramovna Yakubova; Alisher Abdusalimovich Makhmudov; Dinara Islamovna Babajanova; Yulduzkhon Khatamjan Qizi Satvaldieva; Muniskhon Yuldash kizi Usmonova (Journal of Human Rights, Culture and Legal System, 2026)
Global environmental crises and the increasing contribution of private sector activities to ecological degradation create serious challenges for sustainable development in Uzbekistan. Although Uzbekistan has adopted green economy policies and environmental regulations, the implementation of sustainability principles in contractual relationships remains limited due to the absence of clear sustainability standards, weak corporate environmental awareness, and limited judicial practice. This study examines the reconstruction of Uzbekistan’s contract law based on sustainability principles using a normative juridical and comparative legal approach. The findings reveal that Uzbekistan still lacks comprehensive legal mechanisms for integrating sustainability principles into contractual relations and environmental liability systems, while international practices demonstrate that sustainability standards, environmental certification, green procurement, and effective dispute settlement mechanisms can strengthen ecological responsibility in business activities. Therefore, Uzbekistan needs a more integrated sustainability-based contract law framework to support environmental protection and sustainable economic development.